2019
DOI: 10.21203/rs.2.18098/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The reliability and validity of PHQ-9 in patients with major depressive disorder in psychiatric hospital

Abstract: Background: To assess the reliability and validity of Patient Health Questionnaire-9 (PHQ-9) for patients with major depressive disorder (MDD) and to assess the feasibility of its use in psychiatric hospitals in China. Methods: 109 outpatients or inpatients with MDD who qualified the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) criteria completed PHQ-9 and Hamilton Depression Scale (HAMD-17). Two weeks after the initial evaluation, 54 randomly selected patients underwent repea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…Studies have shown measurement invariance by sex and across culturally and linguistically diverse groups 17,18. While research is scarce on the psychometric properties of single items on the scale, a recent study showed good test-retest reliability for each of the items 19…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown measurement invariance by sex and across culturally and linguistically diverse groups 17,18. While research is scarce on the psychometric properties of single items on the scale, a recent study showed good test-retest reliability for each of the items 19…”
Section: Methodsmentioning
confidence: 99%
“…While this practice has its strengths and weaknesses, it sets a standard approach for measuring symptom burden in clinical practice and research. Nevertheless, the PHQ-9 has shown good validity and reliability as well as adaptability to diagnose depression [88]. Based on this clinical approach and in line with the notion of between-study comparability, interspecies homology, and the idea of a transspecies translational matrix for DSM/ICD depression criteria we argue that a similar standardized approach can be devised for laboratory mice.…”
Section: Arguments For a Standardized Depression-like Syndrome In Lab...mentioning
confidence: 80%
“…The PHQ-9 has sound psychometric properties, with good internal consistency (Cronbach's α = .89) and good test–retest reliability, r = .74. 31 …”
Section: Methodsmentioning
confidence: 99%